Thermodynamic analysis of interaction of components in the SIO2-C system: improvement of technical silicon production technological process - Janelidze, Inga; Jandieri, Gigo; Tsertsvadze, Tamar (Physics and Chemistry of Solid State, 2021)
In order to identify ways to improve the technological process of smelting metallic (crystalline) silicon of technical purity, a thermodynamic analysis of the interaction of components in the SiO2-C system is carried out that reveals the main factor in obtaining high-quality technical silicon is the elimination of superposition of the silicon carbonization process that is possible by carrying out a two-stage carbothermal reduction reaction, in that firstly the incomplete reduction of silica (SiO2) by solid carbon (C) is provided, accompanied by the release of new reacting gas components - SiO and CO, the subsequent interaction of which leads to the formation of the target product - technical silicon that is suitable for the production of modern solar energy converters. It is determined that main condition for highly efficient reduction reactions is the fine fractionness (<1 mm) of the used quartzite ore with keeping of a rational temperature range for its carbothermal reduction (1688-2000 K). It has been shown experimentally that the optimal technical solution for the implementation of this reduction process is to performt melting in a special plasma-chemical furnace-reactor with one liquid-metal subconducting electrode, with a reverse vertical feed of the reaction gases released at the first stage. The degree of extraction of silicon was on average 95%, and the degree of its purity was 97.2%.